The Effect of Work Communication, Work Motivation, and Job Satisfaction on the Performance of Medical Employees at Public Health Center of Palembang City (Palembang Ilir Region) - Agung, M. Alvin Prabu (International Journal of Business, Management and Economics, 2022)
This study intends to determine the effect of communication, motivation, and job satisfaction on the performance of Public Health Center employees in Palembang City ( Ilir Palembang region). This research is quantitative and descriptive in nature. Communication, motivation, job satisfaction, and employee performance are the variables used, and 16 indicators are derived from them. This study's sample comprised of 174 medical employees from the Palembang city Public Health Center. Research uses primary data gathered through questionnaires and analyzed using multiple regression approaches. The findings of this study reveal that 1) Work communication, work motivation, and job satisfaction have a significant impact on the performance of public health center medical staff in Palembang City ( Ilir Palembang region) 2) Work communication has a strong favorable impact on the performance of the medical staff at the Palembang City public health center (Ilir Palembang region) 3) The performance of Palembang City public health center medical staff is significantly influenced by their job motivation ( Ilir Palembang region ).4Job satisfaction has a significant impact on the efficacy of medical staff at the public health center in Palembang City ( Ilir Palembang region).